Common Prosperity - Zheng, Yongnian. author. aut Link
XVI, 205 p. 2 illus., 1 illus. in color.
Keywords: This book offers an in-depth analysis of China’s drive for common prosperity from an insider’s perspective. While philosophers and economists have long debated issues of inequality and growth, and societies have evolved from industrial to post-industrial information economies, challenges related to poverty and inequality persist. Major European nations have transitioned from early capitalist societies to modern welfare states, yet similar issues remain unresolved. Professor Zheng Yongnian provides a unique insight into China’s approach to addressing these challenges through the lens of common prosperity. Drawing on newly published materials and empirical research, this book contrasts China's development model with Western welfare states, elucidating both the rationale behind and the implications of these differences. This translated version of Professor Zheng’s recent work, 共同富裕的中国方案 (originally published in Chinese), is an essential read for scholars and policymakers seeking to understand China’s strategy for achieving common prosperity. Zheng Yongnian is a renowned Chinese political scientist and political commentator who has written widely on contemporary China and especially Chinese politics. He currently serves as Presidential Chair Professor and the Founding Director of the Advanced Institute of Global and Contemporary China Studies, the Chinese University of Hong Kong, Shenzhen. Jia Liu (Translator of the book), is an associate research professor in Institute of Public Policy, South China University of Technology.